Apotropaic Practices and the Undead: A Biogeochemical Assessment of Deviant Burials in Post-Medieval Poland - Gregoricka, Lesley A.; Betsinger, Tracy K.; Scott, Amy B.; Polcyn, Marek (PLOS ONE, 2014)
Apotropaic observances-traditional practices intended to prevent evil-were not uncommon in post-medieval Poland, and included specific treatment of the dead for those considered at risk for becoming vampires. Excavations at the Drawsko 1 cemetery (17th–18th c. AD) have revealed multiple examples (n = 6) of such deviant burials amidst hundreds of normative interments. While historic records describe the many potential reasons why some were more susceptible to vampirism than others, no study has attempted to discern differences in social identity between individuals within standard and deviant burials using biogeochemical analyses of human skeletal remains. The hypothesis that the individuals selected for apotropaic burial rites were non-local immigrants whose geographic origins differed from the local community was tested using radiogenic strontium isotope ratios from archaeological dental enamel. 87Sr/86Sr ratios ( = 0.7112±0.0006, 1σ) from the permanent molars of 60 individuals reflect a predominantly local population, with all individuals interred as potential vampires exhibiting local strontium isotope ratios. These data indicate that those targeted for apotropaic practices were not migrants to the region, but instead, represented local individuals whose social identity or manner of death marked them with suspicion in some other way. Cholera epidemics that swept across much of Eastern Europe during the 17th century may provide one alternate explanation as to the reason behind these apotropaic mortuary customs, as the first person to die from an infectious disease outbreak was presumed more likely to return from the dead as a vampire.